(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Fanani Z. M., Rauf A, Maryana N, Nurmansyah A, Hindayana D. 2019. Geographic distribution of the invasive mealybug Phenacoccus manihoti and its introduced parasitoid Anagyrus lopezi in parts of Indonesia. Biodiversitas 20: 3751-3757. Cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae), is an invasive pest detected for the first time in Indonesia in 2010. An exotic parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced and released in 2014 to control the pest. Study was conducted with the objective to determine the geographic distribution of P. manihoti and spread of A. lopezi. Field surveys were conducted on cassava fields in various locations in Lampung, Java, and Nusa Tenggara. Our studies showed that P. manihoti was found to be widely distributed in Lampung, Banten, West Java, Central Java, East Java, West Nusa Tenggara and East Nusa Tenggara. In each location visited, symptoms of P. manihoti infestation as indicated by internode distortion and bunchy top were prominent. Three years following release, parasitoid A. lopezi has established and spread into several cassava growing areas, except East Nusa Tenggara. Parasitism rates varied from 1.50% in West Nusa Tenggara up to 59.18% in East Java. Logistic regression revealed that probability of severe damage by the cassava mealybug was significantly (P<0.05) increased with the increasing abundance of ants.